Empirical evaluation of the law of value. Issue 3 (2nd October 2021) - Johnson, Nathan
Abstract : The law of value is empirically evaluated as it relates to the distribution of capital across industries and their appropriation of surplus value, using US economic census manufacturing data from 1997 through 2017. Strong correlation is demonstrated between the annual surplus value appropriated and mass of capital stock, with the coefficient of determination values ranging 0.75–0.85. Correlation between the product of the effective rate of surplus value and the annual number of turnovers of variable capital versus the organic composition of capital plus one yields coefficient of determination values ranging 0.50–0.61. Factors underlying this correlation are evaluated. Taking market concentration into account only marginally improves the coefficient of determination values. To model results, a theoretical framework is presented in which surplus value is partially retained and partially redistributed across industries. Lastly, the term 'concrete composition of capital' is introduced to denote the ratio of fixed capital to circulating capital, as a counterpart to the organic composition of capital. This ratio increases over time indicating technological progress under capitalism is mobilized to decrease unit production costs, expand the scale of production, and reduce the turnover period of circulating capital as fundamental means of competition.